Predictors of clinical outcomes in patients with sepsis: a retrospective study from a tertiary care hospital in Pakistan - Angez , Meher; Jessani, Sahar; Abbas, Manzar; Akbar, Inaara; Russell Seth Martins,; Ainan Arshad, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess associations between various clinic-demographic factors and clinical outcomes among patients treated for sepsis. Methods: The retrospective study was conducted at the Aga Khan University Hospital, Karachi, and comprised data of all patients aged >18 years diagnosed with sepsis from January to December 2019. Multivariable logistic regression was used to evaluate independent associations between predictors and outcomes. Data was analysed using R packages. Results: Of the 1,136 patients, 621(54.6%) were male and 515(45.3%) were female. The overall mean age was 59.05±16.91 years. Female gender (odds ratio: 1.029; 95% confidence interval: 1.03-1.64) to be an independent predictor of septic shock, while hypertension (odds ratio0.75; 95% confidence interval: 0.59-0.95) emerged as a protective factor. Chronic kidney disease (odds ratio: 1.539; 95% confidence interval: 1.14-2.07) was an independent predictor of prolonged length of stay, while older age appeared to be protective (odds ratio: 0.98; 95% confidence interval: 0.98-0.99). Mortality was associated with a significantly lower odds of Escherichia coli on culture (odds ratio: 0.26; 95% confidence interval: 0.12-0.54). Conclusion: Independent associations were found between specific patient characteristics and adverse clinical outcomes. Key Words: Sepsis, Septic shock, Mortality, Morbidity.